2014
DOI: 10.1177/1078155214534868
|View full text |Cite
|
Sign up to set email alerts
|

Obinutuzumab for chronic lymphocytic leukemia: promise of the first treatment approved with breakthrough therapy designation

Abstract: Obinutuzumab (also known as GA101, afutuzumab, Gazyva) is a humanized, glycoengineered type II monoclonal antibody targeted against CD20. The US Food and Drug Administration has approved obinutuzumab for use with chlorambucil in patients with previously untreated chronic lymphocytic leukemia. The drug is the first treatment to receive approval under the agency's breakthrough therapy designation, a program intended to facilitate and expedite the review and development of therapies for serious and life-threateni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…Currently the treatment of patients with CLL is undergoing fundamental changes (Burger et al, 2017). One promising approach to achieve more durable responses might be the development of glycodendrimers coated with sugar layer which presents unique and functional characteristics (Kakkar and Balakrishnan, 2015;Eichhorst et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Currently the treatment of patients with CLL is undergoing fundamental changes (Burger et al, 2017). One promising approach to achieve more durable responses might be the development of glycodendrimers coated with sugar layer which presents unique and functional characteristics (Kakkar and Balakrishnan, 2015;Eichhorst et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…However, no published data exist to support this report. 39 , 40 A search from the FDA Adverse Event Reporting System database did not yield any data to support this report ( http://www.fda.gov/Drugs/DrugSafety/PostmarketDrugSafetyInformationforPatientsandProviders/ucm111085.htm#O ; http://www.fda.gov/drugs/informationondrugs/approveddrugs/ucm373263.htm ). A Japanese Phase I study of obinutuzumab in refractory B-cell NHL excluded patients with seropositive HBV status, 41 thereby precluding the usefulness of identifying adverse events through clinical trials.…”
Section: Hepatitis B Reactivation In Nhl Therapymentioning
confidence: 96%
“…The elimination of obinutuzumab is likely target-mediated drug disposition. 46 , 47 The relationship between pharmacokinetics and clinical response and/or tumor burden could not be concluded based on Phase I/II trials due to small population numbers. However, the Phase II study reported disappointing response rates in patients with higher tumor burden, suggesting that dosing schedules may be very important for obinutuzumab’s efficacy.…”
Section: Pharmacokineticsmentioning
confidence: 99%
“… 48 Insufficient data exist on the effect of severe renal or hepatic impairment; however, no modifications are expected since monoclonal antibodies are metabolized via ubiquitous proteolytic enzymes. 46 , 47 Further pharmacokinetic data are anticipated with the currently ongoing GAGE study, which is comparing the efficacy and safety of obinutuzumab dosed intravenously at 1,000 mg vs 2,000 mg. Preliminary results at week 32 describe overall response rates (ORRs) of 48.8% and 66.7% ( P =0.0779) among patients receiving 1,000 mg (n=41) and 2,000 mg intravenous infusions (n=39), respectively.…”
Section: Pharmacokineticsmentioning
confidence: 99%
See 1 more Smart Citation